Spirituality in counselling and psychotherapy - Lines, Dennis (SAGE, 2006)
By exploring different perspectives on religion and spirituality, this book provides therapists with the grounding they need to introduce spiritually-centred counselling into their practice. It describes the characteristics of spiritual counselling and covers practical considerations.